2019
DOI: 10.1108/ijoa-08-2018-1499
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 360 feedback appraisal system on organizational justice and sustainability

Abstract: Purpose This paper aims to extend previous results demonstrating a statistically significant causal relationship between the implementation of 360-degree feedback in an organization and employees’ perceptions of organizational justice. It explores the sustainability of this justice, ultimately making it an integral part of the organizational culture. The paper examines whether the previous model (based on relationships among 360-degree feedback, organizational justice and sustainability of organizational justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Respondents rated these eight statements on a seven-point Likert scale (1=very strongly disagree; 7=very strongly agree). Karkoulian et al (2016) and El Haddad et al (2018) found this scale valid and reliable within Lebanon. Despite inclusion in the survey, the present study did not use the results obtained via this scale, as the present study is focused on the relationship between employee engagement and innovation in the presence or absence of 360-degree evaluation and not the perceptions of the respondent relative to 360-evaluation.…”
Section: Methodsmentioning
confidence: 85%
“…Respondents rated these eight statements on a seven-point Likert scale (1=very strongly disagree; 7=very strongly agree). Karkoulian et al (2016) and El Haddad et al (2018) found this scale valid and reliable within Lebanon. Despite inclusion in the survey, the present study did not use the results obtained via this scale, as the present study is focused on the relationship between employee engagement and innovation in the presence or absence of 360-degree evaluation and not the perceptions of the respondent relative to 360-evaluation.…”
Section: Methodsmentioning
confidence: 85%
“…Sustainability: this study uses a five-item scale (Q29-Q33) from the Sustainability Practices Indicator to measure sustainability [143]. This was validated by Karkoulian et al [144] and El Haddad et al [145], and reported to have good psychometric properties. The five items measure the overall focus of the organization on sustainability practices and principles.…”
Section: Methodsmentioning
confidence: 99%
“…The media frenzy surrounding the landmark 1991 Hill-Thomas sexual harassment controversy in the U.S. (McAdams and Beasley 1994) sparked a flurry of research on gendered practices in the workplace (Fitzgerald and Shulman 1993;Harned et al 2002). Since then, scholars delved deeper into gendered workplace substructures and practices in news organizations around the world, both through country-specific investigations and cross-cultural comparisons (Arayssi, Dah, and Jizi 2016;Byerly 2011;Byerly and Ross 2006;Carter 1998;Djerf-Pierre 2005;El Haddad, Karkoulian, and Nehme 2018;Hanitzsch and Hanusch 2012;Jizi and Nehme 2017;Maamari and Saheb 2018;Maamari and Shouweiry 2016;Melin-Higgins 2004;Ross 2014;Steiner 1998;Van Zoonen 1998).…”
Section: Moving Beyond the Body Count: Politics Of Gender In Newsroomsmentioning
confidence: 99%